ANALISIS PENGENDALIAN KUALITAS PRODUK GARMENT PADA PROJECT IN LINE INSPECTOR DENGAN METODE SIX SIGMA DI BAGIAN SEWING PRODUKSI PADA PT BINTAN BERSATU APPAREL BATAM - Monica Elisa Napitupulu; Shinta Wahyu Hati (Politeknik Negeri Batam, 2018)
Abstract Competition among competitors in the increasingly tight business world today encourages companies to develop more effective and efficient way in achieving the goals and objectives that have been set. With the current information and technology consumers become more sensitive about quality and price of a product. Therefore, companies are required to improve the quality of products produced and continuously improve and improve. PT Bintan Bersatu Apparel Batam is one of the manufacturing companies engaged in the production of sportswear. PT Bintan Bersatu Apparel also strives to continuously improve the quality by pressing the product number in the product process in this company. Six sigma as an alternative to the principles of quality control, enabling companies to improve with the actual breakthrough. Six sigma is an important tool for production management to maintain, maintain product quality and improve quality towards zero defect. So six sigma is a method or technique. Which is a new breakthrough in the field of quality management. By using six sigma method can be known quality sportswear produced PT Bintan Bersatu Apparel in 3.55 sigma with damage level of 20,290 for one million production (DPMO). Six sigma quality improvement in this research can be concluded there are three causes of the product: workmanship or constructionas much as 82.04%, fabric as much as 13.82% and accessories as much as 4.14%.In this research data analysis used Six Sigma (DMAIC) method which through five stages that is define, measure, analyze, improve and control.